Meta-Analysis: The Effect of D-Dimer on Mortality in Patients with COVID-19 - Yusuf Ryadi; Setyo Sri Rahardjo; Burhannuddin Ichsan (Journal of Epidemiology and Public Health, 2022)
Background: The severity of COVID-19 can be detected by examining elevated levels of CRP, ferritin, IL-6 and LDH. Elevated D-dimer levels are often found in patients with severe COVID-19 which can predict the occurrence of ARDS (Acute Respiratory Distress Syndrome) and patient mortality. The purpose of this study was to determine how much influence D-dimer levels had on mortality of COVID-19 patients. Subjects and Method: This study used a systematic review and meta-analysis with following PICO, population: patients with a clinical diagnosis of COVID-19. Intervention: high D-dimer level. Comparison: low D-dimer level. Outcome: mortality. The data used were obtained from scientific research articles from Pubmed, Google Scholar, Science Direct, and Proquest electronic databases with a cohort design in 2020 until 2022 and report on aOR in multivariate analysis. The keywords used in the search for scientific articles were “D-dimer level” OR “D-dimer” AND “COVID-19” AND “mortality”. The selection of articles is done by using PRISMA flow diagram. Data were analyzed using Review Manager software version 5.4.1.Results: A total of 12 studies with a cohort design that met the criteria from Asia, America, and Europe were selected for a systematic review and meta-analysis. Based on the meta-analysis, it was found that increased levels of D-dimer (>0.5 g/mL) increased mortality in COVID-19 patients by 6.40 times compared to low levels of D-dimer (≤0.5 g/mL) and was statistically significant (aOR = 6.40; 95% CI= 4.51 to 9.08; p<0.001).Conclusion: Elevated levels of D-dimer may increase mortality risk in COVID-19 patients. Keywords: d-dimer level, d-dimer, covid-19, mortality. Correspondence:Yusuf Ryadi. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: yusuf.ryadi@gmail.com. Mobile: 085715605268.